Offline Device Tracking: A Novel Approach to Locating Lost Devices through Advanced Application Development - Jasimuddin, SK; Tharannum B, Naheeda; Khan, Noor-A-Nabi; Bhattacharya, Sovan (International Journal of Scientific Research in Computer Science and Engineering, 2024)
The ability to track a smart device Smart Phone even when offline increases the chances of recovering that lost device quickly. Maybe the thieves or people who find lost devices often fear to switch on that device(s) or turn them off to avoid detection. The features in Offline tracking can still provide the last updated or known location or update the device owner when the device comes online. Here, in this research article, we have developed an enhanced application-designed system that can track lost devices even when offline or does not connect with any network. Here, we utilized advanced location tracking technologies and robust security features so that the application ensures constant monitoring and protection of Android devices or shields of that device(s). There are various key functionalities used including real-time and historical location tracking, remote device locking, anti-theft measures, etc. Our implemented application can track the addresses of the device(s) in offline mode which was the critical challenge of locating devices without internet connectivity, providing the original users or the owner with comprehensive security and peace of mind. The development process, technical architecture, and user benefits are thoroughly examined here.